A positive electrode sheet insulating coating and preparation method thereof, positive electrode sheet, battery cell, lithium ion battery and electrical equipment
By using nanomaterials and Al2O3 in the insulating coating solution combined with acrylic copolymer, the problem of melting beads and broken strips produced during the laser cutting process of the lithium-ion battery cathode sheet is solved, achieving high safety performance and low cost of the battery core. Production.
Patent Information
- Application Number
- CN202410701655.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-31
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-05-31
AI Technical Summary
The insulating coating of the positive electrode sheet of the existing lithium-ion battery is prone to generate serrated and droplet-like molten beads during laser cutting, resulting in short circuit of the battery cell and insufficient rolling ducting, resulting in broken belts.
An insulating coating solution is used, containing 95-97% Al2O3, 3-5% nanomaterials (such as nano-TiO2 and nano-SnO2) and 650-1000 parts of acrylic copolymer to form an energy-absorbing coating to improve laser cutting efficiency. And mixed with Al2O3 to improve roll extension.
The cutting edge is smooth and burr-free, and there are no molten beads, which reduces the short-circuit rate of the battery core and the risk of belt breakage, improves the safety performance and yield of the battery core, and reduces the production cost.
Smart Images

Figure CN118508010B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a positive electrode sheet insulating coating and a preparation method thereof, a positive electrode sheet, a battery cell, a lithium ion battery and electrical equipment. Background Art
[0002] As the penetration rate of new energy vehicle power batteries continues to increase and the energy storage market develops rapidly, the safety and cost of lithium-ion batteries are particularly important. With the development of power cells, the safety risks in the manufacturing and use of cells are increasingly valued. At present, the main factors limiting the promotion and application of large-capacity power lithium-ion batteries are the battery's cycle performance, safety performance and cost.
[0003] Lithium-ion batteries are composed of five major parts: positive electrode, negative electrode, diaphragm, electrolyte and shell; the diaphragm is located between the positive and negative electrodes, and mainly plays the role of ion conduction and electronic insulation. In the production process of lithium-ion batteries, it is difficult to control the burrs when cutting the electrodes. At the same time, due to factors such as the poor precision of the stacking machine, poor alignment problems frequently occur, resulting in poor contact between the positive and negative electrodes and short circuits in the battery cells. In particular, when the positive aluminum tab overlaps the negative electrode (fully charged), serious thermal runaway problems will occur. Based on the above considerations, the prior art applies an insulating coating on the edge of the positive aluminum tab to prevent thermal runaway. The main component of the existing insulating coating is hydrated aluminum oxide (γ-AlOOH), and its specific surface area is about 3.5g / cm 3 The average particle size is about 3μm, but the particle size of hydrated alumina is too large, and the pole piece is not stretched enough during rolling, which may cause the material area and the tab coating area to break due to inconsistent rolling extension.
[0004] In addition, the existing insulating coating is prone to produce jagged and droplet-shaped molten beads during the laser die-cutting process of the pole piece. Such molten beads are attached to the edge of the pole piece. After being assembled into a battery cell, the molten beads will fall between the pole piece and the diaphragm. After the pole group is hot-pressed, it will pierce the diaphragm and cause a short circuit in the battery cell.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The first object of the present invention is to provide a positive electrode sheet insulating coating, wherein the insulating coating solution can form an energy-absorbing coating on the positive electrode current collector, improve the laser cutting efficiency, and the cutting edge is smooth without burrs or melt beads, and the nanomaterial therein has a small particle size and is similar to Al 2 O 3 Mixed filling can improve the problem of tape breakage due to insufficient rolling extension; and the insulating coating solution contains acrylic copolymer, which has excellent adhesion to the positive electrode current collector, can improve the tensile strength of the positive electrode current collector and reduce the risk of tape breakage.
[0007] The second object of the present invention is to provide a method for preparing an insulating coating of a positive electrode sheet, which has the advantages of simple operation, short process and suitability for mass production.
[0008] A third object of the present invention is to provide a positive electrode sheet having a low short-circuit rate and a high yield rate.
[0009] A fourth object of the present invention is to provide a battery cell having good safety performance, low short circuit rate, low risk of belt breakage, low production cost and high yield rate.
[0010] A fifth object of the present invention is to provide a lithium ion battery having excellent safety performance and low production cost.
[0011] The sixth object of the present invention is to provide an electrical device.
[0012] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0013] The present invention first provides a positive electrode sheet insulating coating, which is mainly prepared from an insulating coating solution, wherein the insulating coating solution includes the following components by mass: Al 2 O 3 95-97 parts, 3-5 parts of nanomaterials, and 650-1000 parts of acrylic copolymer;
[0014] Wherein, the particle size of the nanomaterial is less than 1 μm, and the nanomaterial includes nano-TiO 2 and nano-SnO 2 At least one of .
[0015] Preferably, the particle size distribution range of the nanomaterial is 5 to 40 nm.
[0016] Preferably, the Al 2 O 3 The particle size distribution range is 200~500nm.
[0017] Preferably, the acrylic copolymer comprises acrylic styrene copolymer.
[0018] Preferably, the thickness of the insulating coating is 20-50 μm.
[0019] The present invention further provides a method for preparing the positive electrode sheet insulating coating, comprising the following steps: coating the insulating coating solution and then drying.
[0020] The present invention further provides a positive electrode sheet, comprising a current collector, a tab, and the positive electrode sheet insulating coating;
[0021] Wherein, the electrode tab is connected to the current collector and extends to the outside of the current collector;
[0022] The insulating coating is disposed on an edge region of at least one surface of the current collector close to the pole lug, and the insulating coating extends to a root of the pole lug.
[0023] Preferably, in the edge region, the width of the insulating coating is 3-5 mm.
[0024] Preferably, in the root region of the tab, the width of the insulating coating is 3 to 5 mm.
[0025] The present invention further provides a battery core, comprising the positive electrode sheet insulating coating, or the positive electrode sheet.
[0026] The present invention further provides a lithium ion battery, comprising the battery core.
[0027] The present invention also provides an electrical device, comprising the lithium-ion battery.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The positive electrode sheet insulating coating provided by the present invention is mainly prepared from an insulating coating solution. The nanomaterial in the insulating coating solution has a small particle size and is 2 O 3 Mixed filling can improve the problem of broken tape due to insufficient rolling extension. At the same time, certain types of nanomaterials are not easy to produce molten beads during laser cutting, avoiding the problem of short circuit of battery cells. The insulating coating solution can form an energy-absorbing coating on the positive electrode current collector, improve the efficiency of laser cutting, and the cutting edge is smooth without burrs or molten beads, effectively reducing the short circuit rate of the product and improving the safety performance of the battery cell.
[0030] (2) The positive electrode sheet insulating coating provided by the present invention is mainly prepared from an insulating coating solution, which contains an acrylic copolymer, which has excellent adhesion to the positive electrode current collector, can improve the tensile strength of the positive electrode current collector, reduce the risk of band breakage, significantly improve the processing performance of the positive electrode current collector and increase the yield rate, further reducing the manufacturing cost of the battery cell.
[0031] (3) The positive electrode sheet insulating coating provided by the present invention has the advantages of high insulation, high temperature resistance, chemical corrosion resistance, etc., which can greatly improve the safety performance of the battery cell.
[0032] (4) The positive electrode sheet provided by the present invention has good safety performance, low short-circuit rate, low risk of broken belt, low production cost, and high yield rate. It can effectively solve the problem of short-circuit of positive and negative electrode contact cells, especially the problem of serious thermal runaway when the positive electrode aluminum tab overlaps the negative electrode sheet (fully charged). BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 This is a schematic structural diagram of the positive electrode sheet provided by the present invention. DETAILED DESCRIPTION
[0035] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0036] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0037] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0038] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0039] In a first aspect, the present invention provides a positive electrode sheet insulating coating, wherein the positive electrode sheet insulating coating is mainly prepared from an insulating coating solution, wherein the insulating coating solution comprises the following components by mass: Al 2 O 395-97 parts, 3-5 parts of nano material, and 650-1000 parts of acrylic copolymer.
[0040] Among them, by mass, Al 2 O 3 Including but not limited to any one of 95 parts, 95.5 parts, 96 parts, 96.5 parts, 97 parts or any range values between two of them; nanomaterials include but are not limited to any one of 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts or any range values between two of them; acrylic copolymers include but are not limited to any one of 650 parts, 700 parts, 750 parts, 800 parts, 850 parts, 900 parts, 950 parts, 1000 parts or any range values between two of them.
[0041] Wherein, the particle size of the nanomaterial is less than 1 μm, including but not limited to any point value of 900 nm, 800 nm, 700 nm, 600 nm, 500 nm, 400 nm, 300 nm, 200 nm, 100 nm or a range value between any two of them.
[0042] Furthermore, the nanomaterial includes nano-TiO 2 and nano-SnO 2 At least one of .
[0043] The positive electrode sheet insulating coating provided by the present invention has a nanometer material in the insulating coating solution with a small particle size. 2 O 3Compared with conventional γ-AlOOH, mixed filling can improve the problem of tape breakage due to insufficient rolling extension. At the same time, specific types of nanomaterials are not prone to produce molten beads during laser cutting, avoiding the problem of battery cell short circuit. The insulating coating solution can form an energy-absorbing coating on the positive electrode current collector (it is a high-sensitivity elastomeric acrylic copolymer material that exhibits obvious strain rate effect under a wide range of strain rate conditions, and is a unique super-viscoelastic polymer). In addition, the positive electrode sheet insulating coating is applied to the bottom and cover of the battery shell. By respectively arranging the insulating coating on the bottom shell and the cover, it is possible to save the need to arrange the negative electrode sheet tail roll and high-temperature tape on the outermost layer of the electrode core, thereby increasing the effective space in the shell. The excess space in the shell can be used to coat a slurry with a higher surface density on the base layer of the positive electrode sheet when processing the positive electrode sheet during the production process, thereby increasing the storage capacity of the battery cell, thereby increasing the energy density and storage capacity of the lithium battery, and increasing the cycle life of the battery cell accordingly. In addition, due to the arrangement of the insulating coating, the laser cutting efficiency is improved, the cutting edge is smooth, burr-free, and free of melt beads (or the burr and melt bead phenomenon is greatly reduced), effectively reducing the short circuit rate of the product, and can reduce the risk of puncture short circuit when the lithium battery is subjected to external force, thereby greatly improving the safety performance of the battery cell. Furthermore, the insulating coating solution contains an acrylic copolymer, which has excellent adhesion to the positive electrode current collector, can increase the tensile strength of the positive electrode current collector, reduce the risk of band breakage, significantly improve the processing performance of the positive electrode current collector and increase the yield, further reducing the manufacturing cost of the battery cell.
[0044] In addition, the positive electrode sheet insulating coating provided by the present invention has the advantages of high insulation, high temperature resistance, chemical corrosion resistance, etc., which can greatly improve the safety performance of the battery cell.
[0045] As an oil-based liquid adhesive, acrylic copolymer has good solubility, high strength and high elasticity, as well as good weather resistance and corrosion resistance.
[0046] In some specific embodiments, in order to further improve the problem of tape breakage due to insufficient rolling extension, the particle size distribution range of the nanomaterial is 5 to 40 nm; including but not limited to any point value of 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm or a range value between any two of them.
[0047] In some specific embodiments, the Al 2 O 3 The particle size distribution range is 200-500 nm, including but not limited to any point value of 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, and 500 nm, or the range value between any two of them.
[0048] In some specific embodiments, the acrylic copolymer comprises acrylic styrene copolymer.
[0049] In some specific embodiments, in order to further comprehensively consider ductility, tensile strength, laser cutting efficiency, processing performance and yield, the thickness of the insulating coating is optimized. The thickness of the insulating coating is 20 to 50 μm, including but not limited to any point value of 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, and 50 μm or a range value between any two of them. The positive electrode sheet insulating coating provided by the present invention has a small particle size of the nanomaterial in the insulating coating solution. At the same time, specific types of nanomaterials are not prone to produce melt beads and burrs during the laser cutting process, thereby avoiding the problem of battery cell short circuit and improving the safety performance of the battery cell.
[0050] In some specific embodiments, the nano SnO 2 Including SnO 2 Nanoparticles and / or SnO 2 Nanoflowers.
[0051] In a second aspect, the present invention provides a method for preparing the positive electrode sheet insulating coating, comprising the following steps: applying the insulating coating solution and then drying.
[0052] The preparation method has the advantages of simple operation, short process, and suitability for mass production.
[0053] In some specific embodiments, the viscosity of the insulating coating solution is 2500-6000 mPa / s, including but not limited to any point value of 2500 mPa / s, 3000 mPa / s, 3500 mPa / s, 4000 mPa / s, 4500 mPa / s, 5000 mPa / s, 5500 mPa / s, 6000 mPa / s or a range value between any two of them, which is conducive to coating.
[0054] In some specific implementations, the insulating coating solution is coated on the positive electrode current collector and the positive electrode tab, and then dried to obtain the positive electrode sheet insulating coating.
[0055] In a third aspect, the present invention provides a positive electrode sheet, see Figure 1 As shown, it includes a current collector, a pole ear, and the positive electrode sheet insulating coating.
[0056] Wherein, the electrode tab is connected to the current collector and extends to the outside of the current collector.
[0057] The insulating coating is disposed on an edge region of at least one surface of the current collector close to the pole lug, and the insulating coating extends to the root of the pole lug. It can be understood that the current collector and the pole lug each include two surfaces, and the current collector and the pole lug are connected to form a whole, that is, the current collector and the pole lug are integrally connected to have a first surface and a second surface, and the insulating coating can be disposed only on the first surface or the second surface, or can be disposed on both the first surface and the second surface.
[0058] This can effectively solve the problem of short circuit between positive and negative electrodes, especially when the positive aluminum tab overlaps the negative electrode (fully charged).
[0059] In some specific embodiments, in the edge region, the width of the insulating coating is 3 to 5 mm, including but not limited to any point value of 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm or a range value between any two of them.
[0060] In some specific embodiments, in the root area of the tab, the width of the insulating coating is 3 to 5 mm, including but not limited to any point value of 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm or a range value between any two of them.
[0061] In some specific embodiments, the insulating coating is respectively disposed on an edge region on one side of the upper surface and an edge region on one side of the lower surface of the current collector, and the insulating coating is respectively extended to roots on both surfaces of the tab.
[0062] In some specific embodiments, a positive electrode active material layer is further disposed on at least one surface of the current collector, and the positive electrode active material layer is connected to the insulating coating layer.
[0063] In some specific embodiments, the current collector includes an aluminum current collector, and the electrode tab includes an aluminum electrode tab.
[0064] In a fourth aspect, the present invention provides a battery cell, comprising the positive electrode sheet insulating coating or the positive electrode sheet.
[0065] The battery cell has good safety performance, low short circuit rate, low risk of belt breakage, low production cost and high yield rate.
[0066] In a fifth aspect, the present invention provides a lithium-ion battery, comprising the battery cell.
[0067] The lithium-ion battery has excellent safety performance and its production cost is low.
[0068] In a sixth aspect, the present invention provides an electrical device comprising the lithium-ion battery.
[0069] It is to be understood that the electrical equipment includes any equipment, device or system using the above-mentioned lithium-ion battery.
[0070] The electrical equipment provided by the present invention can be widely used in various fields, such as the field of transportation, the field of electronic products, the field of aerospace, the field of medical treatment or the field of energy storage, etc., and the present invention is not limited to this.
[0071] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0072] Example 1
[0073] This embodiment provides a method for preparing a positive electrode sheet insulating coating and a positive electrode sheet, comprising the following steps: weighing Al 2 O 3 96 parts, nano-TiO 2 4 parts, and 850 parts of acrylic acid styrene copolymer (Dongguan Xinmiao New Materials Co., Ltd.), mixed evenly to obtain an insulating coating solution, wherein nano-TiO 2 The particle size distribution range is 5~20nm, Al 2 O 3 The particle size distribution range is 200-500nm, and the viscosity of the insulating coating solution is 3500mPa / s. The insulating coating solution is coated on both surfaces of the aluminum current collector and the aluminum pole ear, and then dried to obtain the positive electrode sheet insulating coating. There is also a positive electrode active material layer on both sides of the current collector, and the main component of the positive electrode active material layer is lithium iron phosphate (LiFePO 4 ); the positive electrode active material layer is connected to the insulating coating layer.
[0074] The positive electrode sheet prepared in this embodiment includes a current collector, a pole ear and a positive electrode sheet insulating coating; wherein the pole ear is connected to the current collector and extends to the outside of the current collector; the insulating coating is respectively arranged on the edge area of the two side surfaces of the current collector close to the pole ear, and the insulating coating is respectively extended to the root of the two side surfaces of the pole ear, see Figure 1 As shown; the thickness of the insulating coating of the positive electrode sheet is 30 μm; in the edge area, the width of the insulating coating is 5 mm; in the root area of the pole ear, the width of the insulating coating is 4 mm.
[0075] Example 2
[0076] The preparation method of the positive electrode sheet insulating coating and the positive electrode sheet provided in this embodiment is basically the same as that in embodiment 1, except that the nano-TiO 2 Replace with an equal mass of SnO 2 Nanoparticles, including SnO 2 The particle size distribution range of the nanoparticles is 10 to 20 nm.
[0077] Example 3
[0078] The preparation method of the positive electrode sheet insulating coating and the positive electrode sheet provided in this embodiment is basically the same as that in embodiment 1, except that the Al 2 O 3 The mass fraction is replaced by 97 parts, nano-TiO 2 The styrene acrylic acid copolymer was replaced with 3 parts and the styrene acrylic acid copolymer was replaced with 1000 parts.
[0079] Example 4
[0080] The preparation method of the positive electrode sheet insulating coating and the positive electrode sheet provided in this embodiment is basically the same as that in embodiment 2, except that the Al 2 O 3 The mass fraction of SnO is replaced by 95 parts. 2 The nanoparticles were replaced with 5 parts, and the acrylic styrene copolymer was replaced with 700 parts.
[0081] Example 5
[0082] The preparation method of the positive electrode sheet insulating coating and the positive electrode sheet provided in this embodiment is basically the same as that in embodiment 1, except that the nano-TiO 2 The particle size distribution range is 20~40nm.
[0083] Example 6
[0084] The preparation method of the positive electrode sheet insulating coating and the positive electrode sheet provided in this embodiment is basically the same as that in embodiment 2, except that SnO 2 The particle size distribution range of the nanoparticles is 25 to 35 nm.
[0085] Example 7
[0086] The preparation method of the positive electrode sheet insulating coating and the positive electrode sheet provided in this embodiment is basically the same as that in Embodiment 1, except that the thickness of the positive electrode sheet insulating coating is replaced with 20 μm.
[0087] Example 8
[0088] The preparation method of the positive electrode sheet insulating coating and the positive electrode sheet provided in this embodiment is basically the same as that in Embodiment 2, except that the thickness of the positive electrode sheet insulating coating is replaced with 45 μm.
[0089] Example 9
[0090] The positive electrode sheet insulating coating and the method for preparing the positive electrode sheet provided in this embodiment are basically the same as those in Embodiment 1, except that the width of the insulating coating is 3 mm in the edge area and 5 mm in the root area of the electrode ear.
[0091] Comparative Example 1
[0092] The preparation method of the positive electrode insulating coating and the positive electrode provided in this comparative example is basically the same as that in Example 1, except that the nano-TiO 2 Replace with an equal mass of Al 2 O 3 , that is, no nano-TiO was added 2 .
[0093] Comparative Example 2
[0094] The preparation method of the positive electrode insulating coating and the positive electrode provided in this comparative example is basically the same as that in Example 1, except that the Al 2 O 3 Replace with 90 parts and add nano-TiO 2 Replace with 10 portions.
[0095] Comparative Example 3
[0096] The preparation method of the positive electrode insulating coating and the positive electrode provided in this comparative example is basically the same as that in Example 1, except that the nano-TiO 2 The particle size distribution range is changed to 1.5μm~1.6μm.
[0097] Comparative Example 4
[0098] The preparation method of the positive electrode insulating coating and the positive electrode provided in this comparative example is basically the same as that in Example 1, except that the Al 2 O 3 Replaced with an equal mass of γ-AlOOH.
[0099] Comparative Example 5
[0100] The preparation method of the positive electrode sheet insulating coating and the positive electrode sheet provided in this comparative example is basically the same as that of Example 1, except that the acrylic acid styrene copolymer is replaced by PVDF of the same mass.
[0101] Comparative Example 6
[0102] The preparation method of the positive electrode insulating coating and the positive electrode provided in this comparative example is basically the same as that in Example 1, except that the nano-TiO 2 Replaced with nano manganese oxide of equal mass and equal particle size distribution range.
[0103] Comparative Example 7
[0104] The preparation method of the positive electrode sheet insulating coating and the positive electrode sheet provided in this embodiment is basically the same as that in Embodiment 1, except that the acrylic acid styrene copolymer is replaced by ceramic of the same mass.
[0105] Comparative Example 8
[0106] The preparation method of the positive electrode sheet insulating coating and the positive electrode sheet provided in this embodiment is basically the same as that in Embodiment 2, except that the acrylic acid styrene copolymer is replaced by a methacrylate copolymer of equal mass.
[0107] Experimental example
[0108] The rolling breakage rate of the positive electrode sheets prepared in each embodiment and each comparative example, the length of the burrs generated during cutting, and the size of the molten beads generated during the laser die-cutting process were respectively detected. The positive electrode sheets, negative electrode sheets and separators prepared in each embodiment and each comparative example were respectively stacked in a Z-type manner to obtain lithium-ion batteries, and the self-discharge failure rate test was performed. The results are shown in Table 1.
[0109] Table 1 Performance test results
[0110] Group Belt breakage rate / m / times Burr / μm Melt bead size / μm Self-discharge failure rate / % Example 1 4000 7 20 0.5 Example 2 5000 8 18 0.7 Example 3 3000 10 25 1 Example 4 5000 5 16 0.35 Example 5 4000 5 16 0.4 Example 6 3000 9 17 0.7 Example 7 2000 12 19 1.4 Example 8 4000 10 20 1.1 Example 9 5000 11 16 0.4 Comparative Example 1 3000 6 19 1.4 Comparative Example 2 4000 7 10 0.9 Comparative Example 3 4500 4 12 1 Comparative Example 4 3000 9 13 1.6 Comparative Example 5 2000 8 17 2 Comparative Example 6 4000 12 18 0.9 Comparative Example 7 500 20 70 5 Comparative Example 8 5000 7 21 0.8
[0111] It can be seen from Table 1 that the positive electrode sheets and assembled lithium-ion batteries prepared in various embodiments have better comprehensive performance, especially in Example 4, the broken rate, burr and molten bead size, and self-discharge failure rate are significantly reduced. Among them, the low self-discharge failure rate indicates that the risk of physical puncture is small, the anti-puncture performance is good, and the safety performance is high.
[0112] At the same time, compared with Example 1, the broken belt rate, burr size, molten bead size or self-discharge failure rate of Comparative Examples 1 to 8 are all increased, which indicates that the insulating coating solution can form an energy-absorbing coating on the positive electrode collector, improve the laser cutting efficiency, and reduce the risk of broken belts.
[0113] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A positive electrode sheet insulating coating, characterized in that: The insulating coating solution is mainly prepared from an insulating coating solution, wherein the insulating coating solution comprises the following components by weight: 95-97 parts of Al2O3, 3-5 parts of nanomaterials, and 650-1000 parts of acrylic copolymer; Wherein, the particle size distribution range of the nano material is 5 to 40 nm, and the nano material includes at least one of nano TiO2 and nano SnO2; The particle size distribution range of the Al2O3 is 200 to 500 nm; The thickness of the insulating coating is 20 to 50 μm; The insulating coating is arranged on the edge area of at least one surface of the current collector of the positive electrode sheet close to the pole ear, and the insulating coating extends to the root of the pole ear; in the edge area, the width of the insulating coating is 3 to 5 mm; in the root area of the pole ear, the width of the insulating coating is 3 to 5 mm.
2. The positive electrode sheet insulating coating according to claim 1, characterized in that: The acrylic copolymer includes acrylic styrene copolymer.
3. The method for preparing the positive electrode sheet insulating coating according to claim 1 or 2, characterized in that: The method comprises the following steps: coating the insulating coating solution and then drying it.
4. A positive electrode sheet, characterized in that: It comprises a current collector, a pole ear, and a positive electrode sheet insulating coating as claimed in claim 1 or 2; Wherein, the electrode tab is connected to the current collector and extends to the outside of the current collector; The insulating coating is disposed on an edge region of at least one surface of the current collector close to the pole lug, and the insulating coating extends to a root of the pole lug.
5. A battery cell, characterized in that: It comprises the positive electrode sheet insulating coating as claimed in claim 1 or 2, or the positive electrode sheet as claimed in claim 4.
6. A lithium ion battery, characterized in that: Comprising the battery cell as claimed in claim 5.
7. An electrical equipment, characterized in that: Comprising the lithium ion battery as claimed in claim 6.
Citation Information
Patent Citations
Positive plate of lithium ion battery, and preparation method and application thereof
CN105226289A
Positive plate preparation method, positive plate, battery manufacturing method and battery
CN115172673A
Positive plate, preparation method thereof and lithium ion battery
CN115425185A